Kebijakan Industri Malaysia: Kebijakan Industri Mahatir 1988-1985 - Jafar Ahmad (Lembaga Penelitian dan Pengabdian pada Masyarakat, Institut Agama Islam Negeri (IAIN) Kerinci, Jambi, 2015)
ABSTRACT This study aims to understand and explain the policy of the Malaysian economy, particularly industrial policy on bin Mohamad Mahathir administration in the period 1983-1990 in the automotive field. Another objective of this research was to determine and explain the efforts made ​​Mahathir, as Prime Minister of Malaysia, in the run goal of industrialization. The type of this research is descriptive-analytical, ie exposure data that is in the process of industrialization of Malaysia as well as analyze the results in order to be understood. Based on the results of the study show that industrial policy is implemented in Malaysia during the Mahathir administration showed a high state intervention in the industry can give results at least talah taget approach set out in the New Economic Policy. KEYWORDS: Policy of industrial, automotive and Industrial Capital Japan